Labour Legislation and Policies aimed at Reconciling Employees’ Professional Commitments with their Personal and Family Life - Kalamatiev Todor; Ristovski Aleksandar (Университетско Издателство „Св.Климент Охридски", Софија, 2017)
This paper presents illustration of the modern policies for reconciliation of professional responsibilities with personal and family life of workers, i.e. its main subject is the doctrine of establishing “work-family” balance. The process of achieving an appropriate work-family balance consists of several measures and fields of action. Basic measures of work-family balance that can be incorporated in the labour legislation are: flexibility in the organization of the working time oriented towards the needs of workers and leave policies. The authors of this paper reflect on the legal regime of regulating the maternity and parental leave. They analyze the existent labour legislation of the Republic of Macedonia that applies to absence due to pregnancy, birth and parenting (de lege lata) with particular reference to the possible means of regulating the motherhood and parenting (de lege ferenda). Additionally, authors illustrate the forms of flexible organization of working time with a special emphasize on part-time work and other forms of flexible working time oriented towards the needs of workers in order to establish a better work-family balance.
Keywords: work-family balance, flexible working time, maternity and parental leave, unpaid parental leave.